2021
DOI: 10.1111/jocd.14431
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of nasal depressed scars using micro‐plasma radiofrequency technology combined with subcision

Abstract: Background The nose is located in the middle of the face; therefore, nasal scarring will bring a significant psychological impact on patients. Although there are many treatment methods for depressed scars, these methods have varying degrees of efficacy and all carry certain adverse effects. A better treatment method is urgent to be found. In this study, the effect of micro‐plasma radiofrequency technology combined with subcision to treat nasal depressed scars is evaluated. Methods 18 Chinese patients with nasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…RF-assisted subcision was found to be comparable to convention subcision with no risk of hematoma, but entry point burn can occur [ 55 ]. Using microplasma RF technology combined with subcision to treat depressed scars obtained relatively satisfactory results with no adverse effects [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…RF-assisted subcision was found to be comparable to convention subcision with no risk of hematoma, but entry point burn can occur [ 55 ]. Using microplasma RF technology combined with subcision to treat depressed scars obtained relatively satisfactory results with no adverse effects [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The combination of these two effects induces rapid reepithelialization and stimulates the regeneration of dermal collagen, resulting in skin remodeling 5,7 . Due to its efficacy and fewer adverse events, MP FRF is increasingly used to treat acne scars, particularly for patients with darker skin 5–9 . Nevertheless, little evidence has analyzed the factors influencing its effectiveness before and during treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These adverse events have notably decreased when techniques, including radiofrequency (i.e., radiofrequency‐assisted subcision, RF‐subcision, or rsubcision; using thermal energy to aid in the cannula movement), complementary to conventional subcision are implemented 7–9 . Moreover, studies have also demonstrated additional positive effects when the technique is used 7,9–11 …”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 , 9 Moreover, studies have also demonstrated additional positive effects when the technique is used. 7 , 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation